Enhancement of Glucose Metabolism via PGC-1α Participates in the Cardioprotection of Chronic Intermittent Hypobaric Hypoxia - Li, Xuyi; Liu, Yan; Ma, Huijie; Guan, Yue; Cao, Yue; Tian, Yanming; Zhang, Yi (Frontiers in Physiology, 2016)
Background and Aims: Previous studies demonstrated that energy metabolism disturbance impairs cardiac function and chronic intermittent hypobaric hypoxia (CIHH) protects heart against ischemia/reperfusion injury. The present study aimed to test the hypothesis that CIHH protects the heart against ischemia/reperfusion (I/R) injury via improvement of cardiac glucose metabolism. Methods: Male Sprague-Dawley rats received CIHH treatment simulating 5000-m altitude for 28 days, 6 h per day in a hypobaric chamber or no treatment (control). Body weight, fasting blood glucose, blood lipid and glucose tolerance were measured. The left ventricular function of isolated hearts was evaluated during 30 min of ischemia and 60 min of reperfusion using Langendorff method. The mRNA and protein expression involved in cardiac energy metabolism was determined using quantitative PCR and Western blot techniques. Results: 1. There was no difference of body weight, fast blood glucose, blood lipid and glucose tolerance between control and CIHH rats under baseline condition (p > 0.05). 2. The recovery of left ventricular function after I/R was improved significantly in CIHH rats compared to control rats (p < 0.05). 3. The expression of cardiac GLUT4 and PGC-1α was increased but PDK4 gene expression was decreased by CIHH treatment at both mRNA and protein level. Also p-AMPK/AMPK ratio was increased in CIHH rats (p < 0.05). Conclusion: CIHH ameliorates I/R injury through improving cardiac glucose metabolism via upregulation of GLUT4, p-AMPK, and PGC-1α expressions, but downregulation of cardiacPDK4 expression.